Dampak Fenomena E-Commerce Pada Tingkat Penjualan Di Pasar Tradisional Ditinjau Dari Psikologi Dan Ekonomi Islam - Nur'aeni, Nur'aeni Nur'aeni; Ainulyaqin, MH; Edy, Sarwo (ITB AAS INDONESIA Surakarta, 2024)
Sales in traditional markets with the presence of e-commerce has caused a decrease in the number of consumer visitors in traditional markets which has resulted in sales levels decreasing. This is because there is sales competition that occurs on e-commerce platforms which offer very large discount promotions to consumers, thus having a huge impact on traders in traditional markets. The decreasing value of products or goods on e-commerce platforms makes traditional markets less attractive for consumers to visit. The author's aim in carrying out this research is to develop insight according to the topic discussed, namely, to determine the psychological impact experienced by traders in traditional markets on the e-commerce phenomenon and to find out the principles of Islamic economics that can be applied in the context of the e-commerce phenomenon at the sales level. The research method used is descriptive qualitative using field research and this research uses the fishbone method to analyze data. The research results show that traders in traditional markets lack psychological well-being and traders in traditional markets have a high level of religiosity, and in general, electronic trading does not conflict with Islamic law.